THE COMPONENTS OF COMMUNICATIVE COMPETENCE OF UNIVERSITY STUDENTS - Halytska, Mayya M. (Educological discourse, 2015)
The article outlines the competency approach to shaping the content of education, which has become a new conceptual benchmark schools and one of the factors modernization of educational content; it is analyzed the meaning of «competence» and «competencies»; we understood communicative competence of university students as the integral quality of personality that are inherent in a common culture of communication and its specific manifestations in the profession; the components of communicative competence of university students are defined.